JUSTO SIERRA “THE PROFESSOR FROM AMERICA”. FOUNDER OF THE NATIONAL UNIVERSITY OF MÉXICO - Ocampo López, Javier (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
One of the big educators of Mexico in the years of transition between the nineteenth and twentieth century was the humanist Justo Sierra Méndez, founder of the National University of Mexico, current UNAM. He differed for his positivist ideas of freedom, order and progress that he projected in the Mexican education of the Porfiriato. Great writer and pedagogue of the school texts for the Mexican children, to whom he inculcated the "love to the mother land ". This research is interested for the study of his educational ideas that stimulated the freedom, the order and the progress in the mentality of the new generations who did the new political and social Revolution, which indicated the change towards the modernization of Mexico in the contemporary world.